Management techniques and organizational silencing: a manager’s account - Moura-Paula, Marcos; Moreira, Patrícia Aparecida Abreu; Ferraz, Deise Luiza da Silva (Organizações & Sociedade, 2020)
This study analyzes the changes in the relations established in the work environment conditioned by the implementation of management techniques characterizing a Toyotist model and that produced the phenomenon of organizational silence. The story of a financial system worker was used as a guide for structuring our argument. Observations and documents mediated the understanding of the individual story along with the general social relations. Guided by the categories singularity, particularity and universality, we established the links among the worker’s situation, the company’s management techniques and the productive restructuring movement. The results show that the various management techniques were means of silencing built up throughout the worker’s career, as frustrations accumulated and the needs of the work process changed. What in the life of a manager is frustration and silence, in the totalization movement are changes in the being manager marked by the emptying of planning and controlling functions.